A Detailed Overview About the Single-Cell Analyses of Solid Tumors Focusing on Colorectal Cancer - William J. Kothalawala; Barbara K. Barták; Zsófia B. Nagy; Sára Zsigrai; Krisztina A. Szigeti; Gábor Valcz; Gábor Valcz; István Takács; Alexandra Kalmár; Alexandra Kalmár; Béla Molnár; Béla Molnár (Frontiers Media S.A., 2022)
In recent years, the evolution of the molecular biological technical background led to the widespread application of single-cell sequencing, a versatile tool particularly useful in the investigation of tumor heterogeneity. Even 10 years ago the comprehensive characterization of colorectal cancers by The Cancer Genome Atlas was based on measurements of bulk samples. Nowadays, with single-cell approaches, tumor heterogeneity, the tumor microenvironment, and the interplay between tumor cells and their surroundings can be described in unprecedented detail. In this review article we aimed to emphasize the importance of single-cell analyses by presenting tumor heterogeneity and the limitations of conventional investigational approaches, followed by an overview of the whole single-cell analytic workflow from sample isolation to amplification, sequencing and bioinformatic analysis and a review of recent literature regarding the single-cell analysis of colorectal cancers.